FORMATION AND DEVELOPMENTAL STAGES OF LINGUISTIC TERMINOLOGY IN ENGLISH, UZBEK, AND KARAKALPAK LANGUAGES - Koshanova Sakhibjamal Bakhitbaevna (Modern American Journals, 2025)
This article explores the historical formation of linguistic terminology in English, Uzbek, and Karakalpak. It highlights the influence of Latin, Greek, and Arabic traditions and traces how borrowed terms were adapted and localized in each language. By comparing five major stages in English with parallel developments in Uzbek and Karakalpak, the study shows how global and local factors shaped their terminological systems. The findings reveal both universal patterns and culture-specific features in the evolution of linguistic terms.
Keywords: Linguistic terminology; diachronic analysis; English; Uzbek; Karakalpak; borrowing; adaptation; localization; comparative linguistics; language history